Video-based learning activities in pre-service teacher education: effects on self-efficacy and perception of feedback for learning - Manuele Gentile; Gabriella Agrusti; Caterina Fiorilli; Valerio Ghezzi; Giuli Toti (Je-LKS: Journal of E-Learning and Knowledge Society)
Transferring pedagogical knowledge from university courses to school is a complex challenge for many teachers. For this reason, teacher education experts began to recommend integrating practice during pre-service learning activities. Classroom videos could be one of the resources in supporting this critical process. The research involved 84 future teachers randomly assigned to two experimental conditions. In both conditions, the subjects watched two clips in which two teachers interacted with students following a triarchic feedback model: task-oriented feedback, motivational-oriented feedback, and student-oriented feedback. In the first treatment, the participants observed the clips in the context of the knowledge construction (KC) approach. By contrast, in the second treatment, the participants viewed the clips in the context of a direct instruction (DI) strategy. The study had two objectives: understanding the participants’ perception of video-taped teachers’ feedback; and testing the effects of treatments on the participants’ self-efficacy to provide feedback. For the first research goal, the findings partially confirm the three-facet model of feedback. The analysis produces a two-factor solution based on the following components: learning-oriented feedback, and motivational-oriented feedback. Concerning the second research goal, the results show that KC approach seems to produce a higher level of self-efficacy in providing feedback to students. This treatment has a direct impact on the self-efficacy score, with evidence that no teacher and contextual factors directly influence the score or moderate the effects of the approach on the dependent variable. This finding is consistent with studies that address how university courses may positively promote teacher self-efficacy.